The Effectiveness of Reality Group Counseling to Improve Students’ Self-Efficacy - lestari, Puji; Sugiyo, Sugiyo; Purwanto, Edy (Jurnal Bimbingan Konseling, 2022)
Not all students have sufficient self-efficacy to master and finish school tasks. Thus, the present study strived for examining the effectiveness of reality group counseling to improve self-efficacy by performing an experiment involving seven students in this counseling for five sessions. Here, pretest-posttest design was applied, while self-efficacy data were analyzed using Wilcoxon. The results have proved that there was an increase in self-efficacy after the students were given reality group counseling. Hence, counselors are suggested to implement this kind of counseling to improve students’ self-efficacy